2019
DOI: 10.22454/fammed.2019.650493
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Physician Demographic Characteristics on Perceptions of Their Attire

Abstract: Background and Objectives: Few studies address the impact of physician attire on ratings of personality characteristics in the presence of varied physician demographic characteristics (gender, racial/ethnic background). Even fewer have examined the boundaries of acceptable physician attire, given recent loosening of societal standards of dress. Methods: Using an online survey methodology, adult participants (N=505; 45% medical professionals) were recruited. Participants rated target photos depicting a male and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
0
13
0
Order By: Relevance
“… 26 Irrespective of the larger number of woman medical students, a higher woman response rate is not surprising, as women physicians have reported being mistaken for other members of the healthcare team, receptionists or other patients, when wearing certain attire. 21 Other studies have also noted that patient perceptions are more influenced by clothing choices for woman physicians, when compared with their man colleagues. 16 As such, women may have stronger opinions regarding clothing attire and are, thereby, more likely to participate in related research studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 Irrespective of the larger number of woman medical students, a higher woman response rate is not surprising, as women physicians have reported being mistaken for other members of the healthcare team, receptionists or other patients, when wearing certain attire. 21 Other studies have also noted that patient perceptions are more influenced by clothing choices for woman physicians, when compared with their man colleagues. 16 As such, women may have stronger opinions regarding clothing attire and are, thereby, more likely to participate in related research studies.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the literature has highlighted these concerns, with some studies concluding that professional attire can be intimidating or frightening to some patients and even form a nonverbal barrier to communication, by representing a clear hierarchy in the doctor–patient relationship. 21 For the individual, wearing professional attire carries expectations of the role and conveys a message about personal responsibilities. 4 It is not surprising that a few of our students expressed hesitation about these expectations, given their limited medical knowledge and clinical exposure.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the results of previous studies in non-palliative care settings conducted around the world. 1,8,18-28 White coats are the symbols of the physicians and, together with name tags, they can appeal to the patients and the family members that they were seen by trusted medical professionals. They feel relieved to have their reliable doctors make formal rounds on them in a university hospital.…”
Section: Discussionmentioning
confidence: 99%
“…5 A recent study in USA in 2019 reported that physician's name tags were perceived to be crucial in medical settings. 28 Therefore, the main objective of this study was to determine which modifiable and non-modifiable attributes patients prefer in a family physician. In addition, we aimed to understand if patients' sociodemographic characteristics influence their preference for gender, age, nationality of the family physician and importance of greeting with a handshake, of using an identification badge and of wearing a white coat.…”
Section: Strenghts and Limitations Of This Studymentioning
confidence: 99%